UV sizing ceramic slurry for battery pole piece, preparation method of UV sizing ceramic slurry and preparation method of battery pole piece

By using UV-shaped ceramic slurry and ultraviolet curing technology during the lithium-ion battery electrode coating process, the diffusion problem between the ceramic slurry and the active material slurry is solved, and the rapid shaping and stable coating of the ceramic slurry is achieved, and the safety performance and production efficiency of the battery electrode are improved.

CN119614024AActive Publication Date: 2025-03-14JIANGSU PYLON BATTERY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411812512.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

During the coating process of lithium-ion battery electrodes, there is a diffusion problem between the ceramic slurry and the active material slurry, resulting in unstable coating size and hidden dangers of safety performance. Existing improvement methods such as adjusting oven parameters or modifying the air nozzle structure have problems such as uneven edge drying or not completely resolved in ceramic diffusion.

Method used

UV-shaped ceramic slurry is used for battery electrode sheets. By adding 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride and 0.88%-1.05% UV curing glue to the ceramic slurry, and using ultraviolet curing technology during the coating process, a cured film with good breathability is quickly formed and the ceramic slurry is fixed.

Benefits of technology

The rapid shaping of ceramic slurry is achieved, the diffusion of ceramics is reduced, the stability and safety performance of coating are improved, the problem of uneven drying of ceramic slurry is avoided, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614024A_ABST
    Figure CN119614024A_ABST
Patent Text Reader

Abstract

The invention provides UV sizing ceramic slurry for a battery pole piece, a preparation method of the UV sizing ceramic slurry and a preparation method of the battery pole piece, and relates to the technical field of batteries. The UV sizing ceramic slurry for the battery pole piece, provided by the invention, is prepared from the following components in percentage by mass: 28.05 percent to 29.55 percent of ceramic filler, 4.72 percent to 5.07 percent of polyvinylidene fluoride, 0.88 percent to 1.05 percent of UV curing adhesive and the balance of solvent, the UV curing adhesive comprises the following components in percentage by mass: 30%-40% of an active monomer, 2%-3% of a photoinitiator and the balance of urethane acrylate, the active monomers are butyl acrylate and methyl methacrylate, and the mass ratio of butyl acrylate to methyl methacrylate is (18: 6)-(19: 5). The film forming speed of the ceramic slurry is high, the coated and shaped ceramic is not influenced by other coating parameters, and the problem of diffusion between the ceramic slurry and the active material slurry is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a UV-setting ceramic slurry for battery pole pieces and a preparation method thereof, and a preparation method of battery pole pieces. Background Art

[0002] Lithium-ion batteries have developed rapidly in recent years. With the advancement of technology, people have conducted deeper research on the safety performance of batteries. By adding ceramics to both sides of the coating of the pole piece, the safety performance of the battery cell can be greatly improved. Since the slurry and ceramics are in the same solvent system, there must be diffusion when the two slurries come into contact, and the diffusion at the junction of the wet film to the dry film state is uncontrollable, which makes the on-site staff frequently adjust and the effect is poor, affecting the coating size and the CCD identification and judgment of the post-process, and causing hidden dangers to the safety performance of the battery cell.

[0003] At present, the diffusion of ceramics is reduced by adjusting the oven parameters and adopting the high temperature and low wind mode in the first few sections to shape the ceramics in the preheating section and reduce the influence of the wind knife on the diffusion of ceramics.

[0004] The patent (CN202121482425) improves the design of ceramic-coated gaskets, that is, by changing the gasket slurry and ceramic outlet structure to form a drop between the slurry and the ceramic slurry outlet, the outlet height of the ceramic slurry is higher than the slurry outlet, avoiding pressure conflict in the horizontal direction, thereby reducing ceramic diffusion.

[0005] The patent (CN202322192734) modified the structure of the upper nozzle of the coating machine, that is, blocks were added on both sides of the upper nozzle to prevent the air knife from blowing directly on the ceramic, thereby reducing the diffusion of the ceramic.

[0006] Existing problems: After the ceramic coating gasket is improved, there is no interference in the horizontal pressure between the slurry and the ceramic when exiting the die head, but the wet film still has diffusion problems after entering the oven due to the influence of the wind knife; after the nozzle structure on the coating machine is modified, the block structure may cause uneven drying of the edge material area.

[0007] Therefore, it is necessary to propose a simple and stable method to control the diffusion of ceramic slurry.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The first object of the present invention is to provide a UV-setting ceramic slurry for battery pole pieces to solve the above-mentioned technical problems.

[0010] The second object of the present invention is to provide a method for preparing the UV-setting ceramic slurry for the above-mentioned battery pole piece.

[0011] The third object of the present invention is to provide a method for preparing a battery electrode.

[0012] In order to achieve the above objectives, the following technical solutions are adopted:

[0013] In a first aspect, the present invention provides a UV-setting ceramic slurry for a battery pole piece, comprising, by mass percentage: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride (PVDF), 0.88%-1.05% UV curing glue, and the balance being a solvent;

[0014] The UV curing adhesive comprises, by mass percentage, 30%-40% active monomer, 2%-3% photoinitiator, and the balance is polyurethane acrylate;

[0015] The active monomers are butyl acrylate (BA) and methyl methacrylate (MMA), and the mass ratio of butyl acrylate to methyl methacrylate is 18:6-19:5.

[0016] As a further technical solution, the solvent includes N-methylpyrrolidone (NMP).

[0017] As a further technical solution, the photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO).

[0018] As a further technical solution, the UV curing adhesive further includes a stabilizer with a mass percentage of 0.1%-0.25%.

[0019] As a further technical solution, the stabilizer includes hydroquinone (HQ).

[0020] In a second aspect, the present invention provides a method for preparing the UV-setting ceramic slurry for the battery pole piece, wherein the ceramic filler, polyvinylidene fluoride, UV curing glue and solvent are mixed and dispersed to prepare the UV-setting ceramic slurry for the battery pole piece.

[0021] As a further technical solution, after the mixing and dispersion, the UV-setting ceramic slurry for the battery pole piece is also defoamed.

[0022] In a third aspect, the present invention provides a method for preparing a battery electrode sheet, comprising the following steps:

[0023] The electrode slurry and the UV-setting ceramic slurry for the battery electrode are coated on the current collector, and then the battery electrode is prepared after photocuring and drying in sequence.

[0024] As a further technical solution, the light curing method includes ultraviolet light irradiation;

[0025] The wavelength of the ultraviolet light is 250-420nm, and the energy density is 600-1000mJ / cm 2 .

[0026] As a further technical solution, the battery pole piece is coated with UV-setting ceramic slurry on both sides of the pole piece slurry.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) Fast shaping: UV surface curing film-forming technology is used to complete the surface curing film of the ceramic slurry within 3 seconds. The ceramic shaping can be completed before passing through the oven or in the early stage, which can effectively solve the ceramic diffusion problem.

[0029] 2) Good air permeability: The formula design is reasonable, which effectively prevents the appearance problems such as pinholes and foil leakage during the thorough drying process of the ceramic slurry.

[0030] 3) Good weather resistance: The cured film can exist stably in the electrolyte.

[0031] 4) High stability: The quality and rate of ceramic shaping during the coating process are related to the power of the UV lamp and the content of UV glue, which is independent of the coating process parameters and close to a constant, and has good stability.

[0032] 5) Low cost: Compared with conventional formulas and coating equipment, only a small amount of UV curing glue needs to be added to the ceramic slurry, and a certain length of UV lamp needs to be added to the coating machine. This can solve the ceramic diffusion problem at a low cost, saving manpower and material resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic diagram of the implementation of UV setting ceramic slurry of the present invention;

[0035] Figure 2 Schematic diagram of the pole piece structure.

[0036] Icon: 1-substrate; 2-back roller; 3-die; 4-ceramic edge; 5-UV lamp; 6-ear; 7-active substance coating. DETAILED DESCRIPTION

[0037] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0038] In a first aspect, the present invention provides a UV-setting ceramic slurry for a battery pole piece, comprising, by mass percentage: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride, 0.88%-1.05% UV curing glue, and the balance being a solvent;

[0039] The UV curing adhesive comprises, by mass percentage, 30%-40% active monomer, 2%-3% photoinitiator, and the balance is polyurethane acrylate;

[0040] The active monomers are butyl acrylate and methyl methacrylate, and the mass ratio of butyl acrylate to methyl methacrylate is 18:6-19:5.

[0041] The UV-setting ceramic slurry for battery pole pieces provided by the present invention uses an ultraviolet lamp to quickly cure the UV glue on the ceramic surface into a breathable adhesive film before the ceramic slurry enters the oven. The ceramic slurry is quickly set by the adhesive film, and the ceramic after setting during coating is not affected by other coating parameters, thereby solving the diffusion problem between the ceramic slurry and the active material slurry.

[0042] The UV-setting ceramic slurry for battery pole pieces provided by the present invention has good chemical weather resistance, and the cured film can stably exist in the electrolyte; it has good air permeability, and effectively prevents the appearance problems such as pinholes and foil leakage during the thorough drying process of the ceramic slurry; it has a fast film-forming speed, and can better adapt to the fast production rhythm of coating.

[0043] In some optional embodiments, the solvent includes but is not limited to N-methylpyrrolidone, or other solvents well known to those skilled in the art.

[0044] In some optional embodiments, the photoinitiator includes but is not limited to 2,4,6-trimethylbenzoyldiphenylphosphine oxide, or other photoinitiators known to those skilled in the art.

[0045] In some optional implementations, the UV curing adhesive further includes a stabilizer, and the mass percentage of the stabilizer may be, for example, but not limited to, 0.1%, 0.2% or 0.25%.

[0046] In some optional embodiments, the stabilizer includes but is not limited to hydroquinone.

[0047] By adding stabilizers, the reactivity of UV glue is reduced, the storage capacity is improved, and the slurry is prevented from being affected by the environment before coating to complete curing.

[0048] In a second aspect, the present invention provides a method for preparing the UV-setting ceramic slurry for the battery pole piece, wherein the ceramic filler, polyvinylidene fluoride, UV curing glue and solvent are mixed and dispersed to prepare the UV-setting ceramic slurry for the battery pole piece.

[0049] The preparation method is simple and convenient.

[0050] In some optional embodiments, after the mixing and dispersing, the UV-setting ceramic slurry for the battery pole piece is further defoamed.

[0051] The present invention does not impose any specific limitation on the defoaming method. For example, defoaming can be performed by vacuuming.

[0052] In a third aspect, the present invention provides a method for preparing a battery electrode sheet, comprising the following steps:

[0053] The electrode slurry and the UV-setting ceramic slurry for the battery electrode are coated on the current collector, and then the battery electrode is prepared after photocuring and drying in sequence.

[0054] The pole piece preparation method provided by the present invention can quickly shape the ceramic slurry before entering the oven, greatly reducing glue overflow, and can reduce the risk of cracking by low-temperature baking in the oven preheating stage, thereby improving product yield.

[0055] In some optional embodiments, the light curing method includes ultraviolet light irradiation;

[0056] The wavelength of the ultraviolet light is 250-420nm, and the energy density is 600-1000mJ / cm 2 .

[0057] In some optional embodiments, the battery pole piece is coated with UV-setting ceramic slurry on both sides of the pole piece slurry.

[0058] The present invention is further described below by means of specific examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0059] Example 1

[0060] A UV-setting ceramic slurry for battery pole pieces, comprising, by mass percentage: 29.05% ceramic filler (nano ceramic powder), 4.9% polyvinylidene fluoride, 1.05% UV curing glue, and the balance N-methylpyrrolidone;

[0061] The UV curing adhesive comprises, by mass percentage, 35% active monomer (butyl acrylate and methyl methacrylate in a mass ratio of 18:6), 2.5% 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 0.2% hydroquinone, and the balance is polyurethane acrylate;

[0062] The preparation method is as follows:

[0063] Preparation of adhesive solution: Stir at 30rpm, add some TPO and HQ pre-dissolved in NMP, the remaining NMP, polyurethane acrylate, active monomer, and PVDF. After adding, increase the dispersion line speed to 15m / s and stir for 60min. If there are bubbles after the end, open a vacuum of -85kpa ​​for 30min.

[0064] Preparation of ceramic slurry: Stir at 30rpm, add nano-ceramic slurry in batches of 50%, 30%, and 20%. After each addition, the dispersion line speed is 15m / s, and the dispersion is carried out for 20min. The last dispersion is 160min. After stirring, a vacuum of -85kpa ​​is applied for 60min.

[0065] Example 2

[0066] A UV-setting ceramic slurry for battery pole pieces, comprising, by mass percentage: 28.05% ceramic filler (nano ceramic powder), 4.72% polyvinylidene fluoride, 0.95% UV curing glue, and the balance N-methylpyrrolidone;

[0067] The UV curing adhesive comprises, by mass percentage, 30% active monomer (the mass ratio of butyl acrylate to methyl methacrylate is 18.5:5.5), 2% 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 0.1% hydroquinone, and the balance is polyurethane acrylate;

[0068] The preparation method is the same as Example 1.

[0069] Example 3

[0070] A UV-setting ceramic slurry for battery pole pieces, comprising, by mass percentage: 29.55% ceramic filler (nano ceramic powder), 5.07% polyvinylidene fluoride, 1.05% UV curing glue, and the balance N-methylpyrrolidone;

[0071] The UV curing adhesive comprises, by mass percentage, 40% active monomer (butyl acrylate and methyl methacrylate in a mass ratio of 18:6), 3% 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 0.25% hydroquinone, and the balance is polyurethane acrylate;

[0072] The preparation method is the same as Example 1.

[0073] Comparative Example 1

[0074] The difference from Example 1 is that no UV curing glue is added.

[0075] Comparative Example 2

[0076] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 17:7.

[0077] Example 4

[0078] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 19:5.

[0079] Comparative Example 3

[0080] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 16:8.

[0081] Comparative Example 4

[0082] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 20:4.

[0083] Comparative Example 5

[0084] The difference from Example 1 is that the amount of UV curing adhesive used is 1.23%.

[0085] Example 5

[0086] The difference from Example 1 is that the amount of UV curing adhesive used is 0.88%.

[0087] Comparative Example 6

[0088] The difference from Example 1 is that the amount of UV curing adhesive used is 5%.

[0089] Comparative Example 7

[0090] The difference from Example 1 is that the amount of UV curing adhesive used is 2%.

[0091] Test Example 1

[0092] The electrode slurry (active material (lithium iron phosphate) 93.70%, adhesive (polyvinylidene fluoride) 3.24%, dispersant (polyvinyl pyrrolidone) 0.57%, conductive slurry (carbon nanotubes) 0.57%, conductive agent (carbon black) 1.92%; solvent is NMP (N-methylpyrrolidone)) and the UV-setting ceramic slurry for the battery electrode of the above embodiment or comparative example are coated on the current collector. The specific steps are as follows:

[0093] The ceramic slurry is transferred to a coating tank, and the ceramic is coated on a substrate 1 conveyed by a backing roller 2 by extrusion coating using a die head 3. The ceramic is coated on both sides of the active slurry, such as Figure 1 ; The coated ceramic is transferred to the working area of ​​UV lamp 5 (250-420nm, energy density 600-1000mJ / cm 2 The UV glue on the surface of the ceramic slurry is triggered by the ultraviolet light to complete the film formation on the surface of the ceramic; the ceramic slurry and active slurry after the shaping enter the coating oven to complete full drying to obtain a positive electrode sheet without ceramic diffusion. The structure of the positive electrode sheet is as follows Figure 2 As shown, the active material coating 7 is located in the middle, and the ceramic edge 4 and the pole ear 6 are located on both sides.

[0094] The following tests were performed on the prepared pole pieces:

[0095] 1) Appearance: Visually inspect the surface quality of the ceramic surface after film formation, measure the number of pinholes per unit length, and grade them according to severity. A1, A2, A3, A4, and A5 become more severe in turn, and A1 has no pinholes.

[0096] 2) Whether the ceramic diffuses: Prepare low-concentration ceramic slurry, measure the diffusion width of the solidified ceramic, and grade it according to the severity. B1, B2, B3, B4, B5 become more serious in turn, and B1 has no diffusion.

[0097] 3) Electrolyte immersion: After curing and drying, the ceramic is immersed in electrolyte for 48 hours to observe whether the outer film expands, falls off, or changes color. The electrolyte is composed of solvent (30% ethylene carbonate, 40% ethyl methyl carbonate, 5% propylene carbonate, 25% diethyl carbonate), lithium salt 1.2 mol / L lithium hexafluorophosphate, and additives (0.5% lithium bis(fluorosulfonate)imide, 1.8% vinylene carbonate) by mass fraction.

[0098] 4) Ceramic flexibility: A long ceramic pole piece with a width of 2 cm was made. The pole piece used a cylinder with a diameter of 5 cm and a winding force of 100N. The deformation during the pole piece processing was simulated, and the ceramic was visually observed to see if it cracked or fell off after winding.

[0099] The results are shown in Tables 1 and 2.

[0100] Table 1

[0101]

[0102] In the process of adjusting the ratio of soft monomer BA and hard monomer MMA, the soft monomer can improve the adhesion and flexibility of the glue, but will reduce the density of the film; the hard monomer can improve the density and hardness of the film, and too high a ratio will reduce the toughness of the film. It can be seen from the examples and comparative examples that the optimal active monomer ratio of BA:MMA is 18:6-19:5. For the convenience of preparation, the optimal BA:MMA ratio is 18:6. The appropriate active monomer ratio can maintain good flexibility, no shedding, and no cracking during the battery processing and in the battery electrolyte.

[0103] Table 2

[0104]

[0105]

[0106] During the process of adjusting the UV glue content, due to the unconventional curing of the UV glue, after the surface is cured and filmed, the solvent inside evaporates during the subsequent drying process. If the film thickness is too thick, the air permeability will decrease, a large number of pinholes will be formed, and in severe cases, foil leakage will occur. If the UV curing glue is too little, the curing effect will be unstable and the film formation will be discontinuous. It can be seen from the embodiments and comparative examples that the optimal content of the UV curing glue is 0.88%-1.05%, and the optimal content is preferably 1.05%. With the appropriate UV curing glue content, the surface film thickness is adapted and continuous, and there is no abnormal appearance after the ceramic slurry is completely dried.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A UV-setting ceramic slurry for battery pole pieces, characterized in that: Calculated by mass percentage, it includes: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride, 0.88%-1.05% UV curing adhesive, and the balance is solvent; The UV curing adhesive comprises, by mass percentage, 30%-40% active monomer, 2%-3% photoinitiator, and the balance is polyurethane acrylate; The active monomers are butyl acrylate and methyl methacrylate, and the mass ratio of butyl acrylate to methyl methacrylate is 18:6-19:

5.

2. The UV-setting ceramic slurry for battery pole pieces according to claim 1, characterized in that: The solvent includes N-methylpyrrolidone.

3. The UV-setting ceramic slurry for battery pole pieces according to claim 1, characterized in that: The photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

4. The UV-setting ceramic slurry for battery pole pieces according to claim 1, characterized in that: The UV curing adhesive also includes a stabilizer in an amount of 0.1% to 0.25% by weight.

5. The UV-setting ceramic slurry for battery pole pieces according to claim 4, characterized in that: The stabilizer includes hydroquinone.

6. The method for preparing the UV-setting ceramic slurry for battery pole pieces according to any one of claims 1 to 5, characterized in that: The ceramic filler, polyvinylidene fluoride, UV curing adhesive and solvent are mixed and dispersed to prepare UV-setting ceramic slurry for battery pole pieces.

7. The preparation method according to claim 6, characterized in that: After the mixing and dispersion, the method further includes defoaming the UV-setting ceramic slurry for the battery pole piece.

8. A method for preparing a battery electrode, characterized in that: The following steps are involved: The electrode slurry and the UV-setting ceramic slurry for battery electrode according to any one of claims 1 to 5 are coated on the current collector, and then the battery electrode is prepared after photocuring and drying in sequence.

9. The preparation method according to claim 8, characterized in that: The light curing method includes ultraviolet light irradiation; The wavelength of the ultraviolet light is 250-420nm, and the energy density is 600-1000mJ / cm 2 .

10. The preparation method according to claim 8, characterized in that: The battery pole piece is coated with UV-setting ceramic slurry on both sides of the pole piece slurry.

Citation Information

Patent Citations

  • Coated ceramic gasket

    CN216137597U

  • Mechanism for improving coating of ceramic sol

    CN220919826U

  • Electrode paste for lithium secondary battery, electrode and lithium secondary battery

    CN106848209A

  • Lithium ion battery pole piece coated with ceramic paste and preparation process thereof

    CN107681117A

  • Preparation method of ultraviolet curing modified polyolefin battery diaphragm

    CN114243207A